Gender, Conflict, and Identity in British Women’s Accounts of the Crimean War - Mawby, Darcie (2022)
This thesis examines women’s accounts of the Crimean War to explore the ways that women navigated ideas of femininity in military spaces. It also investigates the relationship between femininity, military space, and British society during the war and its afterlife into the early twentieth century. Rather than treating individuals, such as Mary Seacole, or distinct groups, such as the military hospital nurses, largely separately as much scholarly literature has tended to do, this thesis brings a wide range of individuals, texts, and spaces into dialogue. Drawing on accounts written by soldiers’ wives, officers’ wives and family, military nurses, and nursing applicants, this thesis follows Eleanor Gordon and Gwyneth Nair’s approach to the social history of gender relations. It goes beyond considering women’s participation in the war in relation to the nineteenth-century ideology of “separate spheres”, by considering the diverse networks and discourses that shaped women’s lived experiences of the war and their accounts of it. As such, it identifies important interconnections resulting from shared experiences of military spaces and interrogates the nature of individuals’ and communities’ relationships to nineteenth-century gender ideologies in practice. It also provides insight into the highly subjective nature of women’s war experiences, by foregrounding the role that factors such as class, labour, personal relationships, and wider public attention played in shaping these. In a time when ideology dictated that women were suited to private, domestic lives, the Crimean War provided opportunities and spaces for individuals to renegotiate these parameters. Women were able to navigate ideals of femininity, construct roles for themselves in wartime which could bear little resemblance to the feminine ideal, and even find acceptance for doing so, precisely because the war was experienced and constructed through far more complex social and cultural matrices.